Psychoactive Substance Uses and Risky Sexual Behaviors among Street-Connected Children in Kinshasa, Democratic Republic of Congo: Prevalence and the Associated Factors - Rodriguez Kambamba Mboma; Reagan Moluantuan Ndwaya; Dan Nkelenda Mulumba; Rodrigue Kumbu Khonde; Joseph Wamu Oyombo; Dieudonné Mukendi Mpunga (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2026)
Background: The street-connected children in Kinshasa endure very precarious living conditions and are exposed to a very high risk of violence, substance use, and risky sexual behaviors. In this population, the use of psychoactive substances (PAS) is a key determining vulnerability to HIV and other sexually transmitted infections. Aims: This study sought to ascertain the prevalence of psychoactive substance use and identify the associated factors related with risky sexual behaviors among street-connected children aged 10-24 years in Kinshasa. The dependent variables encompassed risky sexual practices, including the ingestion of psychoactive substances (PAS). Substance use disorders, age, gender, education level, and exercise performed are among the independent variables. Methods: An analytical cross-sectional study was executed from June and December 2024 with 425 street-connected children selected using snowball sampling. Data were gathered through a standardized questionnaire. We used descriptive statistics, chi-square tests, and logistic regression analysis to find factors that were related (p < 0.2). Results: An extremely high percentage of people used drugs, alcohol, and tobacco: 85.9 % for tobacco, 79.9 % for alcohol, and 32.5 % for drugs. The average age at which people started drinking alcohol was 11 ± 3 years, and the average age at which they started smoking tobacco was 12 ± 3 years. The average age at which girls and boys first had sex was 14 ± 4 years and 13 ± 2 years, respectively. Almost all of the people who took part (98 %) said they had more than one sexual relationship, and 83.7 % said they didn’t always use condoms. In multivariate analysis, risky sexual behavior was significantly associated with being under 20 years of age (10-14 years: OR = 4.11; 95 % CI [1.72 - 9.87]; p = 0.002 and 15-19 years: OR = 2.05; 95 % CI [1.05 - 4.04]; p = 0.037), male sex (OR= 1.78; CI [0.98 - 3.22]; p= 0.055); inactivity (OR= 3.63; 95 % CI [1.66 - 7.94]; p= 0.001) and alcohol consumption (OR= 3.96; 95 % CI [1.27 - 12.38]; p= 0.018). The duration of street life and peer influence were the primary factors related with psychoactive substance usage. Conclusion: Substance use and high-risky sexual behaviors are very common among street-connected youngsters in Kinshasa. These findings underscore the pressing necessity for integrated and multisectoral interventions aimed at substance use prevention, sexual health education, and the social reintegration of street-connected children.